A new report on the clasper movements of a captive Sand Tiger Shark Carcharias taurus (Lamniformes:Odontaspididae) and a possible reason for the behaviour - Colbachini, Helen [UNESP]; Gutierrez, Rafael Caprioli; Pizzutto, Cristiane Schilbach; Gadig, Otto Bismarck Fazzano [UNESP] (Wildlife Information Liaison Development Society, 2018)
Elasmobranchs present four clasper movements, which can be seen in different contexts from mating to no obvious reason. Three movements have been reported in Carcharias taurus and here the first occurrence of clasper flaring in this species is described. Clasper flaring was observed while other species were in a reproductive state and their aggressive behaviour towards the subject of this study was also observed
Keywords: Agonistic behavior; Carcharias taurus; elasmobranch; Grey Nurse Shark; reproduction; reproductive behaviour